Assessment of heavy metal content in public drinking water from different water authorities - Dharmaraj, Dorairaj. (Universiti Malaysia Sarawak (UNIMAS), 2007)
Water is a natural resource that cannot be taken for granted. Many a war has been fought over the control of water. This study point to the prevalence of heavy metal contamination in, both, raw water and treated drinking water in Sarawak. Many heavy metal contaminants in water are also anthropogenically introduced into water courses as a result of human habitations and their livelihood practices, such as agriculture, involvements in industries, habitation, and so on.